Proza Katarzyny Tubylewicz - Boczkowska, Magdalena (Tematy i Konteksty, 2015)
The paper entitled ‘The prose of Katarzyna Tubylewicz’ is dedicated to the co-authoress of the anthology of the short stories 'Jestem mamą – zbiór prawdziwych historii o macierzyństwie', and the authoress of two novels: 'Własne miejsca' (2005) and 'Rówieśniczki' (2014), who some critics would like to see as the reviver of the so-called 'prose of the centre'. The authoress of the article analyses the above-mentioned novels referring to – among other things – a discussion which took place in ‘Gazeta Wyborcza’, and which had been initiated by the famous manifesto entitled ‘Alice Munro would not stand a chance here’. Its authors demand that the literary critics should enter into a dialogue with popular literature and dispose of the misconception that literature written by women is worse. They are also for the revival of 'the prose of the centre', which – in their opinion – since Tokarczuk’s 'Prawiek i inne czasy' has been missing.